"I felt like I was being watched": The hypervisibility of Muslim students in higher education. Issue 3 (23rd February 2021) - Chaudry, Izram
Abstract: This paper focuses on the ways in which Islamophobia operates within a university environment and how it is impacting the everyday experiences for a sample of British Muslim students. Qualitative methods were adopted to interview a select of participants attending a Russell Group institution located in Northern England. The findings revealed that they most frequently encountered subtle and inconspicuous forms of racism. Otherwise known as microaggressions. The narratives suggested that the participants experienced Islamophobic microaggressions relating to their appearances. The methods and behaviours that the perpetrators utilised included maintaining excessive distance, peculiar staring and hurling racial jokes. What emerged was how the accumulation of religious prejudice had taken its toll on the participants psychological being as they claimed to have developed symptoms pertaining to mental health issues. The discussion explored a number of avenues as to how the participants could mitigate any long-lasting detriment. The options included conversing with members of the Ummah ; and accessing university support systems for professional help.